METABOLIC SYNDROME AND CARDIOVASCULAR DISEASE: THE RELATIONSHIP BETWEEN PHYSICAL EXERCISE AND INTERLEUKIN-6. (Fiep Bulletin - online, 2016)
Environmental factors and modifiable lifestyle, including diet and exercise, have been shown to be crucial in the prevention of metabolic syndrome and Cardiovascular Diseases. Metabolic syndrome consists of metabolic disorders, coagulation disorders and is characterized by a proinflammatory state, an increase of circulating levels of cytokines, such as interleukin-6. Methodology: Literature review by subject. Publications in English, Portuguese, Italian and Spanish scientific articles researched in MEDLINE (PUBMED), BIREME (LILACS) and SCIELO 2008-2014 and books published from 2005 to 2010 were used. Objective: Review about the Metabolic Syndrome and Cardiovascular diseases and the relationship of these diseases with exercise and serum levels of Interleukin-6. Conclusion: The muscle tissue is a source of production of interleukin-6 during prolonged exercise and muscle glycogen concentration can be a determining, regulating this cytokine response to physical exercise, benefiting individuals who practice regularly, preventing the Metabolic Syndrome and Cardiovascular Diseases.
Keywords: Metabolic Syndrome; Cardiovascular Diseases; Exercise; Interleukin-6.